Influence of Live Streaming Characteristics on Continuance Intention to Shopping on TikTok - Az Zahra, Nadhilah Putri; Chairy, Chairy (RSF Conference Series: Business, Management and Social Sciences, 2023)
As a new business model, live-streaming shopping has high commercial value. Although research on live streaming shopping has been in great demand, a holistic model that explains why audiences are willing to continue using such new selling formats is limited. According to interactive marketing theory, this research proposes a theoretical model to examine the impact of live-streaming characteristics on trust and how trust affects the audience's continuance intention in the live-streaming shopping scenario. The data were collected using an online questionnaire spread out through social media such as TikTok, Facebook and Instagram. A partial Least Square (PLS) approach was used to analyze the data. From the result, live streaming characteristics used in this study are interactivity, informativeness, entertainment, perceived relevance, visibility, professionalization, and originality. Empirical results (N=325) reveal that trust is affected by the seven characteristics of live-streaming shopping that affect continuance intention. Questionnaires were distributed through social media to get Indonesian respondents who had used live-streaming shopping on TikTok. However, it is found that live-streaming genres do not moderate the impact of trust towards continuance intention. Research findings indicate how trust is built to generate optimal consequences in live-streaming shopping.